Relationships between junction temperature, electroluminescence spectrum and ageing of light-emitting diodes. (15th March 2018) - Vaskuri, Anna; Kärhä, Petri; Baumgartner, Hans; Kantamaa, Olli; Pulli, Tomi; Poikonen, Tuomas; Ikonen, Erkki
Abstract: We have developed spectral models describing the electroluminescence spectra of AlGaInP and InGaN light-emitting diodes (LEDs) consisting of the Maxwell–Boltzmann distribution and the effective joint density of states. One spectrum at a known temperature for one LED specimen is needed for calibrating the model parameters of each LED type. Then, the model can be used for determining the junction temperature optically from the spectral measurement, because the junction temperature is one of the free parameters. We validated the models using, in total, 53 spectra of three red AlGaInP LED specimens and 72 spectra of three blue InGaN LED specimens measured at various current levels and temperatures between 303 K and 398 K. For all the spectra of red LEDs, the standard deviation between the modelled and measured junction temperatures was only 2.4 K. InGaN LEDs have a more complex effective joint density of states. For the blue LEDs, the corresponding standard deviation was 11.2 K, but it decreased to 3.5 K when each LED specimen was calibrated separately. The method of determining junction temperature was further tested on white InGaN LEDs with luminophore coating and LED lamps. The average standard deviation was 8 K for white InGaN LED types. We have six years of ageing data available for a set of LED lamps and we estimated the junction temperatures of these lamps with respect to their ageing times. It was found that the LEDs operating at higher junction temperatures were frequently more damaged.